Economics of childbirth. (17th April 2013) - Fahy, Michael; Doyle, Orla; Denny, Kevin; Mcauliffe, Fionnuala M.; Robson, Michael
Abstract Background Increasing birth rates have raised questions for policy makers and hospital management about the economic costs of childbirth. Objective The purpose of this article is to identify and review all existing scientific studies in relation to the economic costs of alternative modes of childbirth delivery and to highlight deficiencies in the existing scientific research. Method We searched Cochrane, Centre for Reviews and Dissemination, EconLit, the Excerpta Medica Database, the Health Economic Evaluations Database, MEDLINE and PubMed. Results Thirty articles are included in this review. The main findings suggest that there is no internationally acceptable childbirth cost and clinical outcome classification system that allows for comparisons across different delivery modes. Conclusion This review demonstrates that a better understanding and classification of the costs and associated clinical outcomes of childbirth is required to allow for valid comparisons between maternity units, and to inform policy makers and hospital management.